desktop application for managing a dental clinic - Ahdibi, Halima Saadia; Toumiate, Imane; LOUNNAS, Bilal: Sypervisor (University of Mohamed Boudiaf, M’sila, 2024)
In this thesis, we developed a desktop application aimed at managing a private dental and oral surgery clinic. This application is designed to facilitate and enhance healthcare services in the clinic through numerous features it offers, such as easy clinic management and data access. We encountered some obstacles after developing the design on Figma, but fortunately, we overcame them by finding alternatives. We tried several models of our system, and we ended up choosing the most appropriate and efficient one. We also designed the application in a way that we ensured the simplicity of the user interfaces so that users could use our application easily. Our project is not yet final, and we are still working on completing it and adding more features and enhancements. These include an appointment reminder system for patients via text messages, the ability to analyze data to improve medical performance, and support for a multilingual interface to facilitate use. We strive to achieve the highest possible performance improvements, and this is one of the areas we will focus on in the future.
Keywords: desktop application; for managing; a dental clinic